Inhibition of TBK1/IKKε Promotes Regeneration of Pancreatic β-cells. Issue 1 (December 2018) - Xu, Jin; Jia, Yun-Fang; Tapadar, Subhasish; Weaver, Jessica; Raji, Idris; Pithadia, Deeti; Javeed, Naureen; García, Andrés; Choi, Doo-Sup; Matveyenko, Aleksey; Oyelere, Adegboyega; Shin, Chong
Abstract β-cell proliferation induction is a promising therapeutic strategy to restore β-cell mass. By screening small molecules in a transgenic zebrafish model of type 1 diabetes, we identified inhibitors of non-canonical IκB kinases (IKKs), TANK-binding kinase 1 (TBK1) and IκB kinase ε (IKKε), as enhancers of β-cell regeneration. The most potent β-cell regeneration enhancer was a cinnamic acid derivative (E)-3-(3-p henylbenzo[c]i soxazol-5-yl)a crylica cid (PIAA), which, acting through the cAMP-dependent protein kinase A (PKA), stimulated β-cell-specific proliferation by increasing cyclic AMP (cAMP) levels and mechanistic target of rapamycin (mTOR) activity. A combination of PIAA and cilostamide, an inhibitor of β-cell-enriched cAMP hydrolyzing enzyme phosphodiesterase (PDE) 3, enhanced β-cell proliferation, whereas overexpression of PDE3 blunted the mitogenic effect of PIAA in zebrafish. PIAA augmented proliferation of INS-1β-cells and β-cells in mammalian islets including human islets with elevation in cAMP levels and insulin secretion. PIAA improved glycemic control in streptozotocin (STZ)-induced diabetic mice with increases in β-cell proliferation, β-cell area, and insulin content in the pancreas. Collectively, these data reveal an evolutionarily conserved and critical role of TBK1/IKKε suppression in expanding functional β-cell mass.